Russian invasion of Ukraine: impact on stock trade volume and price of Indonesian coal companies / Batsyeba Sundari, Rahmawati and Budiasih - Sundari, Batsyeba; -, Rahmawati; -, Budiasih (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
The war resulted in inflation and fuel shortages. The coal sector was significantly affected by Russia's incursion into Ukraine. The objective of this study is to examine the disparities in the price and trading volume of PT Bumi Resources stocks prior to and following Russia's hostile actions towards Ukraine. The utilized observation data spans a period of 48 weeks preceding and following the announcement of Russian military intervention in Ukraine. Descriptive analysis is employed to provide a detailed description of the chosen variables, while the paired t test is utilized to ascertain the presence of any disparities. The research findings indicate notable disparities in the price and trading volume of PT Bumi Resource shares prior to and after to the announcement.